MSME’s sustainability during the Covid 19 pandemic: the roles of Islamic crowdfunding, financial literacy and technology adoption/ Norasekin Abd Rashid ... [et al.] - Abd Rashid, Norasekin; Mamat @ Ibrahim, Norzawani; Hasim, Norhasdalina; Zainal Abidin, Maziana (Universiti Teknologi MARA Selangor, 2022)
Due to the excessively strict procedures enforced by financial institutions and government authorities, the MSMEs in Malaysia are struggling to survive especially during the Covid 19 pandemic. To address this critical issue, with the advancement in technology, entrepreneurs have become more independent and creative in raising capital through a process known as crowdfunding. Hence, this study intends to examine the relationship between Islamic crowdfunding, financial literacy, and technology adoption towards MSME’s sustainability during the Covid 19 pandemic. Based on the random sample of 259 MSMEs, we assessed the correlation between all the variables using SmartPLS 3.3. The results show that Islamic crowdfunding, financial literacy, and technology adoption have affected the MSMEs’ sustainability positively. The results also indicate that financial literacy was the most influential factor towards MSMEs’ sustainability during the Covid 19 pandemic situation.